PENGEMBANGAN MEDIA INTERAKTIF BERBASIS PENDEKATAN KONSTRUKTIVISME PADAI MATERIIALJABARIKELASIVII SMP/MTs - Ramadhani Fajriyati (Departemen Matematika, 2022)
Interactive learning media is an innovation to help students build mathematical understanding in today's digital era. This study aims to develop interactive learning media based on a constructivism approach to valid and practical algebraic material for seventh grade students of SMP/MTs. The type of research used is development, using Plomp model which consists of a preliminary research stage and a development or prototyping stage. The preliminary research stage is the initial stage to determine the characteristics of the media. The development or prototyping stage is the stage for designing interactive media, a formative evaluation is carried out for evaluation. The results showed that constructivism-based interactive learning media for algebraic material had a valid category, and a very practical category. Based on these results, it can be concluded that the interactive learning media produced are valid and practical. Keywords- Interactive Learning Media, Constructivism, Plomp, Algebra